Pengaruh Permainan Tradisional Dan Hasil Belajar Terhadap Kecerdasan Interpersonal Anak Usia 6-8 Tahun Kelas 1-2 - Elva M Sumirat; Nurul Aini MM Sodik; Mita Sari (Lembag, 2024)
The objective of this research is to find out the differences between Traditional Games and Learning results in the interpersonal intelligence of children 6-8 years old. The research used the experimental method with a 2x2 factorial design. The research findings are as follows, 1). Interpersonal intelligence Students group 6-8 years old who use traditional game goro are higher than student group who use traditional game tengge-tengge, 2). There is an interaction effect between traditional games and learning results toward interpersonal intelligence of children 6-8 years old, 3). Interpersonal intelligence Students group 6-8 years old who have high learning results which using traditional game goro are higher than using traditional tengge-tengge, 4). Interpersonal intelligence Students group 6-8 years old who have low learning results which using traditional game tengge-tengge are higher than using traditional goro.